Testicular cancer epidemiology in developing countries. Review of the literature (2017)
OBJECTIVE: Testicular cancer (TC) is the most common cancer in men between 15 and 44 years. It has been reported that the incidence of TC is rising. The aim of this article is to determine the epidemiology of TC in Colombia. METHODS: A literature review o